Prolonged ventricular asystole: a rare adverse effect of hydrocodone use - Sudhakaran, Sivakumar; Surani, Saherish S; Surani, Salim R (The American journal of case reports, 2014)
Prolonged ventricular asystole is a rare vagal reaction caused by hydrocodone use. Sinus bradycardia is a characteristic presentation of the vasovagal response; examples of other presentations include arrest or atrioventricular block. Physicians need to be aware of ventricular asystole due to vagally-mediated atrioventricular block caused by hydrocodone or other opiates. We present a case of prolonged ventricular asystole in a young patient due to a vasovagal reaction caused by the hydrocodone found in the hydrocodone/acetaminophen combination. Ventricular asystole can be a rare complication of hydrocodone found in hydrocodone/acetaminophen. Physicians need to be aware of this adverse effect, rather then resorting to expensive diagnostic interventions.